The aesthetics of leadership - Ladkin, Donna (Henry Stewart Talks, 2010)
Defining what is meant by the term: 'Aesthetics of Leadership', How is an 'aesthetic of leadership' created? -What is the role of language in creating a leadership aesthetic?, What is the role of body language in creating a leadership aesthetic?, Investigating Barack Obama's leadership aesthetic, How might leaders use the idea of 'the aesthetics of leadership' in their day-to-day engagement with others?